Predictive factors for outcome in HER2-low breast cancer patients after neoadjuvant chemotherapy - Shao, Yingbo; Guan, Huijuan; Luo, Zhifen; Yu, Yang; He, Yaning; Chen, Qi; Liu, Chaojun; Zhu, Fangyuan; Liu, Hui (Frontiers in Oncology, 2025)
ObjectiveThe present study aimed to evaluate the predictive factors that predict outcomes of HER2-low breast cancer patients who did not achieve pathological complete response(pCR) after neoadjuvant chemotherapy (NAC).MethodsThis study included patients with HER2-low breast cancer who received NAC from January 2017 to December 2020. Analysis of the clinicopathological features, NAC response and outcome of the patients were retrospectively analyzed. Univariate and multivariable Cox analysis were used to determine factors that predict outcomes of HER2-low breast cancer patients who did not exhibit pCR.Results293 Asian patients were included. The proportion of patients with hormone receptor (HR) positive and triple negative breast cancer (TNBC) among HER2-low patients was 75.8% and 24.2%, respectively. The pCR rate of HR positive cases was significantly lower than TNBC (27.5% vs. 53.5%, P=0.000). The patients who obtained pCR after NAC showed better disease-free survival(DFS) (5-year DFS 93.9% vs. 83.1%, p=0.039). For patients not achieving pCR, multivariable analysis showed that Miller/Payne (MP) grading system (hazard ratio: 0.094; 95% CI: 0.037-0.238; p=0.000) and HR status (hazard ratio: 2.561; 95% CI: 1.100-5.966; p=0.029) were significant independent predictors for DFS. Additionally, The MP grading system was also an independent predictor of overall survival (OS) (hazard ratio: 0.071; 95% CI: 0.019-0.260; p=0.000).ConclusionsThe results of our study show that pathological assessment following NAC offers valuable insights into the survival outcome of HER2-low breast cancer. According to these findings, responses to NAC should be considered when choosing systemic treatment for patients with HER2-low breast cancer.